Approaches And Strategies For Long-Term Adaptability At Jnt Company Matahari Raya Medan Branch - Alya Rusana Pane; Amanda Syahfitri; Hari Adrian Tarigan; Najamuddin Sinuhaji; Resa Kania Br Tarigan; Tety Januarti (SEAN Institute, 2024)
This study aims to examine the impact of operational adaptability strategies on customer satisfaction at JNT Matahari Raya Medan, considering the growing demand for fast and reliable logistics services. Using a quantitative approach, data were collected through survey involving employees and customers, utilizing questionnaire that measure adaptability strategy indicators such as employee training, delivery efficiency, technology adoption, and service innovation. The results indicate a significant relationship between operational adaptability strategies and customer satisfaction levels. Delivery efficiency and clear tracking information was found to play a substantial role in enhancing customer satisfaction, while innovation and the abilities to adapt to changing customer needs also contributed to strengthening customer loyalty. Consequently, JNT Matahari Raya Medan is encouraged to continue developing more optimal adaptability strategies to maintain customer satisfaction and loyalty amid increasing competition.